Pengaruh Penyuluhan Kesehatan tentang Kebersihan Genitalia terhadap Upaya Pencegahan Keputihan pada Remaja Putri di SMAN 3 Bukittinggi - Yunita Zahra; Irma Fidora; Rista Nora (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Vaginal discharge is a discharge other than blood from the vaginal opening out of habit, whether smelly or not, and accompanied by local itching. The prevalence of vaginal discharge in South Asian adolescents is 70%, in Indonesia around 90% of women have the potential to experience vaginal discharge and as many as 60% are experienced by adolescent girls (Prabawati, 2019). Indonesian Adolescent Reproductive Health (SKRRI) shows that women aged 15-24 years experience vaginal discharge as much as 31.8%. The latest data from West Sumatra taken from PKBI (Indonesian Family Planning Association) in Padang in 2013 that women who experience vaginal discharge are 80% of women of childbearing age and 20% of married women. For data on vaginal discharge in Bukittinggi City taken based on previous research conducted at MAN 3 Agam, the incidence of vaginal discharge that occurs in adolescent girls is 71.7%. Many adolescents who experience vaginal discharge do not know about this problem. Efforts to achieve positive behavior change in handling and preventing vaginal discharge are health counseling about genital hygiene. The purpose of this study was to determine the effect of health counseling on genital hygiene on efforts to prevent vaginal discharge in adolescent girls at SMAN 3 Bukittinggi. This type of research is quantitative using a pre-experiment design with a pretest posttest design approach. The number of samples in this study were 30 people. Data collection using questionnaires and data analysis using paired t-test. The results showed a positive effect of health counseling on genital hygiene on efforts to prevent vaginal discharge in adolescent girls at SMAN 3 Bukittinggi as evidenced by the significant value of p (0.000) < α (0.05) and 95% confidence interval. For this reason, it is expected that respondents should be more open if they have problems related to reproductive health, especially regarding vaginal discharge.